Nilai Nilai Pendidikan Karakter Dalam Kitab Adabul Mufrad Karya Imam Al Bukhari Dan Relevansinya Terhadap Pembentukan Akhlak - Agung Madani; Alfi Taufik (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Character education has become a crucial issue in response to increasing moral challenges in modern society. Islam provides a strong moral foundation through the Prophet’s traditions, one of which is compiled in Adabul Mufrad by Imam al-Bukhari. This study aims to identify the values of character education contained in Adabul Mufrad and analyze their relevance to moral formation. This research employs a qualitative method with a library research approach. Data were collected through an in-depth examination of hadith texts in Adabul Mufrad, supported by relevant literature on character education and Islamic morality, and analyzed using a descriptive-analytical technique through classification and interpretation of the content. The findings reveal that Adabul Mufrad contains fundamental character education values, including honesty, responsibility, compassion, patience, humility, respect for parents, and social care. These values are highly relevant to moral development and can be internalized in personal, social, and educational contexts. The study concludes that Adabul Mufrad is not only of religious and normative significance but also has practical implications as a source of character education for fostering noble character in the modern era.